Nanny Piggins and the Runaway Lion - Spratt, R.A. (Australia Random House Publishers, 2010)
Nanny Piggins tames a lion and a lion tamer. She revolutionists the sport of ski jumping, introduces hot-pink leotards to the local Neighborhood Watch, demonstrates trapeze skills on a moving bus, plays badminton with a wok and teaches Shakespeare a thing or two about how to write a play. All while thwarting Mr Green's attempt to send her favourite children to Nicaragua (she does find it wearisome having to put him in his place constantly).
Keywords: Nannies -- Swine -- Brothers and sisters